PELABELAN TOTAL TITIK AJAIB GRAF HASIL KALI KARTESIUS DARI GRAF SIKEL - nita, maria; Soelistyo, R. Heri (MATEMATIKA, 2010)
A vertex-magic total labeling of graph , with the vertices and the edges is the bijection from to the set of integers , and for each vertex in satisfying , is the vertex that adjacent with , then named a magic constant in . The sum of the label of and the labels of all edges incident to the is the same for all vertices of and named vertex-magic total graph. Vertex-magic total labeling of cartesian products of cycles, with the type , with and is odd are the labeling to the and the concept used to label is -vertex antimagic total labeling and to label it is used vertex magic total labeling of cycles, with the cycle is odd.